2020
DOI: 10.5194/acp-20-9393-2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of biomass burning on upper tropospheric carbon monoxide: a study using MOCAGE global model and IAGOS airborne data

Abstract: Abstract. In this paper, the fate of biomass burning emissions of carbon monoxide is studied with the global chemistry–transport model MOCAGE (MOdélisation de Chimie Atmosphérique à Grande Échelle) and IAGOS (In-Service Aircraft for a Global Observing System) airborne measurements for the year 2013. The objectives are firstly to improve their representation within the model and secondly to analyse their contribution to carbon monoxide concentrations in the upper troposphere. At first, a new implementation of b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Chemistry-transport modeling (CTM) offers a solution to cope with such limitations, hence the extensive use of CTM scenario approaches to describe and assess the transport and impact of biomass burning emissions on atmospheric composition at the global, e.g., [19][20][21] and regional scale, e.g., [22][23][24]. In particular, the CHIMERE model [25] is extensively used for the study of atmospheric impacts of large biomass burning events in several areas of the world, with examples of application in Africa [26], Russia [27][28][29], and the Mediterranean [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Chemistry-transport modeling (CTM) offers a solution to cope with such limitations, hence the extensive use of CTM scenario approaches to describe and assess the transport and impact of biomass burning emissions on atmospheric composition at the global, e.g., [19][20][21] and regional scale, e.g., [22][23][24]. In particular, the CHIMERE model [25] is extensively used for the study of atmospheric impacts of large biomass burning events in several areas of the world, with examples of application in Africa [26], Russia [27][28][29], and the Mediterranean [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, SOFT-IO is a scientific tool which couples FLEXPART 20-day backward plumes of air masses for all the aircraft tracks with global anthropogenic and fire emission inventories for CO, and has been used in various studies (e.g. Cussac et al, 2020;Petetin et al, 2018) to investigate and quantify anthropogenic and biomass burning origin in CO measurements. For the entire IAGOS flight track, SOFT-IO v1.0 estimates the CO contribution (in ppb) of recent (≤ 20 days before) worldwide emissions.…”
Section: Model-calculated Parameters For the Iagos Data Points: Potenmentioning
confidence: 99%
“…Thereby, the emissions were increased globally in all NMVOC emission sources by 50 %. In both simulations, the meteorological fields were specified by the European Centre for Medium-Range Weather Forecasts (ECMWF) European Reanalysis Interim (ERA-Interim; Dee et al, 2011), and all simulations were initialized on 1 May 2017.…”
Section: Emacmentioning
confidence: 99%
“…In the contemporary understanding, the chemical composition of the confined system of the AMA is dominated by enhanced amounts of tropospheric trace gases, such as water vapor (H 2 O) and carbon monoxide (CO), which are transported to higher altitudes (Santee et al, 2017). Several model studies have identified the impact of different source regions and long-range transport on the AMA, either with artificial tracers (e.g., Vogel et al, 2015Vogel et al, , 2016Vogel et al, , 2019 or, e.g., CO as a proxy (Pan et al, 2016;Cussac et al, 2020). However, large discrepancies are observed in ASM radiative heating rates between different reanalyses (Randel and Jensen, 2013), which result in uncertainties in diabatic vertical transport.…”
mentioning
confidence: 99%